2019
DOI: 10.1200/jgo.19.00099
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Solid Tumor Incidence in Ukraine 30 Years After Chernobyl

Abstract: PURPOSE There is limited knowledge of the long-term health effects of the Chernobyl nuclear power plant accident that occurred more than 30 years ago in Ukraine. This study describes trends in the incidence of solid organ malignancy in Ukraine and the five regions most affected by the radioactive fallout. METHODS The National Cancer Registry of Ukraine was queried for age-standardized incidence rates (ASIRs) of solid organ malignancy in Ukraine and the regions of Kyiv, Chernihiv, Zhytomyr, Rivne, and Volyn cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 18 publications
1
18
0
1
Order By: Relevance
“…We observed about 30% increase in age‐, urban/rural status‐, and rayon‐average 5‐year lagged cumulative dose adjusted breast cancer incidence rates per decade both in Belarus and Ukraine. Breast cancer incidence trends in both countries showed age‐, time‐ and urban lifestyle patterns similar to those observed worldwide 20,31‐33 …”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…We observed about 30% increase in age‐, urban/rural status‐, and rayon‐average 5‐year lagged cumulative dose adjusted breast cancer incidence rates per decade both in Belarus and Ukraine. Breast cancer incidence trends in both countries showed age‐, time‐ and urban lifestyle patterns similar to those observed worldwide 20,31‐33 …”
Section: Discussionsupporting
confidence: 68%
“…Breast cancer incidence trends in both countries showed age-, time-and urban lifestyle patterns similar to those observed worldwide. 20,[31][32][33] We found no evidence of increased breast cancer incidence in relation to rayon-average 5-year lagged cumulative breast dose nei- 34 We also observed some decrease in RR estimates with dose in Ukraine after 2000 where the relocation process from the most contaminated settlements after 2000 was incomplete and delayed, compared to Belarus. 35 Our study results did not show a higher radiation-related risk of breast cancer in women 45 years or younger at the time of the accident as compared to those women who were older than 45 years.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…[31], Leung et al [14] and Krystle et al [13] reported an increased incidence of PC and other tumors. 137 Cs concentrates in edible plants and fruit.…”
Section: Fig 7 Autoradiogram Showing 137mentioning
confidence: 99%